Human-Centric Functional Modeling and Metatheories of Psychology - Williams, Andy (My University, 2021)
The newly emerging science of Human-Centric Functional Modeling provides an approach towards modeling systems that is hypothesized to maximize human capacity to understand and navigate complexity in those systems. This paper provides an overview exploring how Human-Centric Functional Modeling might be applied in psychology, and how this increase in capacity to understand complexity might be achieved within the discipline. One potential application is increasing our capacity to compare metatheories of psychology. Given that developing and/or understanding any one particular metatheory of psychology can be a life-long achievement, and assuming that understanding and comparing more than one or two such metatheories might be outside the cognitive capacity of most individuals, one potential key area of usefulness for Human-Centric Functional Modeling is that it provides a single universal way of modeling the human organism and its psychology so that all such metatheories might be compared in each context of their use in order to collectively converge on a single meta-understanding of psychology and of clinical interventions in psychology that best reflect observations.
Keywords: functional state space; General Collective Intelligenc; Human-Centric Functional Modeling; metatheory